2017
DOI: 10.1002/ca.22876
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and anatomical variations of accessory navicular bone in patients with foot pain: A retrospective radiographic analysis

Abstract: The accessory navicular (AN) is an accessory ossicle anatomically located on the medial side of the foot, proximal to the navicular and continuous with the tibialis posterior tendon. It is occasionally a source of pain and local tenderness. Knowledge of the AN and its morphological variations can help identify the source of a patient's symptoms and prevent misinterpreting them as fractures. Foot radiographs from 1,240 patients who presented in two centers with chronic foot pain, or persistent pain developed af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 25 publications
(66 reference statements)
1
25
3
Order By: Relevance
“…The accessory navicular bone prevalence is estimated to be between 4 to 25% [34,35]. The incidence of the accessory navicular bone in the current study fits into the mentioned range.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The accessory navicular bone prevalence is estimated to be between 4 to 25% [34,35]. The incidence of the accessory navicular bone in the current study fits into the mentioned range.…”
Section: Discussionsupporting
confidence: 73%
“…The incidence of the accessory navicular bone in the current study fits into the mentioned range. An overrepresentation of accessory navicular bone in patients with tibialis posterior tendon insufficiency can be noticed [34]. We observed no statistically significant differences regarding connections in patients with and without the accessory navicular bone, indicating a separate developmental origin [36].…”
Section: Discussioncontrasting
confidence: 49%
“…Estimated prevalence has been set in between 4 and 21% [1–3]. A recent long series by Kalbouneh et al estimates it as 20.9% [4].…”
Section: Midfootmentioning
confidence: 99%
“…Many authors actually consider it a type II that has fused to the tubercle. It may become symptomatic by irritation of the surrounding tissues, with possible adventitial bursa formation [10] and flat foot deformity [4] (Fig. 3).…”
Section: Midfootmentioning
confidence: 99%
“…Anatomical variation is a normal presentation of body structure with morphological features different from those described in the literature. It involves many types and forms of variations, including muscle structure, attachments, and innervation, ligament attachments and morphology, blood vessel branching, nerve patterns and positions, and bone morphology and accessory bones [1][2][3][4][5][6][7]. It has been found that some of these anatomical variations are closely related to ethnic groups [8].…”
Section: Introductionmentioning
confidence: 99%